2016
DOI: 10.1007/s00418-016-1408-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired SIRT1 promotes the migration of vascular smooth muscle cell-derived foam cells

Abstract: The formation of fat-laden foam cells, contributing to the fatty streaks of the plaques of atheroma, is the critical early process in atherosclerosis. The previous study demonstrated that vascular smooth muscle cells (VSMCs) contain a much larger burden of the excess cholesterol in comparison with monocyte-derived macrophages in human coronary atherosclerosis, as the main origin of foam cells. It is noteworthy that VSMC-derived foam cells are deposited in subintima but not media, where VSMCs normally deposit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…SIRT1 is an antiarteriosclerotic factor that can regulate cholesterol metabolism and reduce the inflammatory response [25]. TRPV1 activation by capsaicin can inhibit the formation and migration of VSMC-derived foam cells by protecting SIRT 1 and inhibiting NF-kB signaling [26]. In macrophage-derived foam cells, Zhao et al showed that TRPV1 agonists could upregulate the Figure 2.…”
Section: Regulation Of Lipid Metabolismmentioning
confidence: 99%
“…SIRT1 is an antiarteriosclerotic factor that can regulate cholesterol metabolism and reduce the inflammatory response [25]. TRPV1 activation by capsaicin can inhibit the formation and migration of VSMC-derived foam cells by protecting SIRT 1 and inhibiting NF-kB signaling [26]. In macrophage-derived foam cells, Zhao et al showed that TRPV1 agonists could upregulate the Figure 2.…”
Section: Regulation Of Lipid Metabolismmentioning
confidence: 99%
“…Although a study has reported that BYHWS is involved in a neuron protective role through suppression of the P53 pathway (46), to our knowledge, no previous studies have investigated whether BYHWS directly influences SIRT1 expression. It has been demonstrated that SIRT1's predominate function is in delaying aging and suppressing arterial remodeling (26,27,33). Our further experiments revealed that down regulation of SIRT1 levels by siRNA-knockdown elevated cellular migration/invasion and MMP-2, leading to enhancement in senescent HA-VSMCs.…”
Section: Discussionmentioning
confidence: 71%
“…A low SIRT1 level contributed to not only an acceleration of cellular senescence but also increased capacity for cellular migration and invasion (25)(26)(27)(28)33). Thus we measured the levels of SIRT1 protein in the Ang II-induced HA-VSMCs.…”
Section: Byhws Delayed the Down-regulation Of Sirt1 Protein In Senescmentioning
confidence: 99%
“…This may hold promise as a novel therapeutic approach for carotid atherosclerosis since the SIRT1/AMPK pathway is key to a number of vasculoprotective processes. In particular, SIRT1 is the nicotinamide adenosine dinucleotide (NAD)-dependent deacetylase that has been associated with inhibition of the proatherogenic VSMC foam cell formation possibly through the suppressing of the nuclear factor kappa B (NF-κB) signalling pathway 38 . AMPK is the main energy-sensing kinase in all eukaryotic cells and has been implicated in stabilizing atherosclerotic plaques through the inhibition of the mammalian target of rapamycin (mTOR) signalling pathway 39 .…”
Section: Discussionmentioning
confidence: 99%